The importance of adopting IAS 7 in the management of cash flows of an economic institution A case study of the Aurens Batna for 2015-2016 - Beroual, Boumadain (Milev Journal of Research and Studies, 2018)
IAS 7 is considered one of the most important standards approved by the IASB. It is intended to provide information on the historical development of a company's cash and cash equivalents based on a cash flow statement. This table shows the cash flows of a given year in operating, investing and financing activities that would enable the Company to continue its cash flows effectively by assessing its ability to create cash and cash equivalents the future, Know the causes of inflows and outflows, Know the ability to meet their future obligations. In this article, we will attempt to clarify the importance of adopting IAS 7 by the company in managing its cash flows. Or the dairy of the Aures will be the place of the case study on which we build the results of this study .